Factors contributing to stress and anxiety among students in UiTM Sarawak Campus Samarahan & Samarahan 2 / Nurulain Othman and Nur Hazimah Sapawi - Othman, Nurulain; Sapawi, Nur Hazimah (2024)
The purpose of the study is to examine the factors contributing to stress and anxiety among students in UiTM Campus Samarahan and Samarahan 2. The study was conducted from March 2023 to January 2024. This study utilized simple random sampling techniques to gather the survey data. The results of the study revealed three important findings. Firstly, the majority of respondents agreed that the factors of stress and anxiety such as academic pressure, financial burden, unhealthy lifestyles and lack of social support, do affect stress and anxiety. Furthem1ore, the primary factor of stress and anxiety is the academic pressure and there is no significant difference between the mean level of stress and anxiety between male and female.